Analysis and implementation of the Autotransformer Forward-Flyback converter applied to photovoltaic systems. (December 2019) - López del Moral, D.; Barrado, A.; Sanz, M.; Lázaro, A.; Fernández, C.; Zumel, P.
Highlights: The AFF converter presents a step-up and step-down voltage transfer function. Reduction of voltage stresses in diodes and MOSFET. ZCS and soft switching characteristics in the diodes and MOSFET. Use of a single controlled switch and only a driver. The theoretical analysis is verified through a 225 W prototype. Abstract: The Distributed Maximum Power Point Tracking (DMPPT) architecture is employed to overcome the mismatching phenomena in grid-tied photovoltaic (PV) installations. In this kind of architecture, a DC-DC module integrated converter (MIC) manages each PV panel. Thanks to the DC-DC converters, the differences between PV panels do not influence others, maximizing the amount of harvested power. The MIC requirements to make this kind of solutions profitable are voltage step-down and step-up capability, low cost and high efficiency. This paper analyses the Autotransformer Forward-Flyback (AFF) converter. This converter is considered as a MIC candidate for fulfilling the requirements above. The study of the AFF converter includes the steady-state analysis and the small signal analysis in continuous conduction mode. The advantages of the AFF converter are the capability of voltage step-down and step-up; the simplicity since it only includes a single controlled switch; the use of an autotransformer; good dynamic performances and the soft switching characteristics in all the diodes. The paper includes a detailed AFF converter step-by-step design procedure, applied to 100 kW grid-tied PV installation, in which the effect of shadows has been considered. A 225 W AFF converter prototype validates the theoretical analyses, achieving an efficiency up to 94.5%.